Online Communities of Practises as Agricultural Information Platforms: A Case Study of Indonesian Shrimp Farmers during the COVID-19 Pandemic - Lee Guenwoo; Pratiwi Ayu; Farikhah; Suzuki Aya; Kurosaki Takashi (Taylor & Francis, 2025)
Amidst the challenges of the COVID-19 pandemic, this study examines the potential of Online Communities of Practises (OCoPs) for providing agricultural extension services. Using a unique dataset of 1,574 shrimp farmers, including members of one of Indonesia's largest public OCoP Facebook groups, we found that despite the pandemic, Indonesian farmers continue to rely primarily on their neighbours for farming information, utilising OCoPs only as a complementary resource. This reliance may stem from the fragmented and codified nature of information shared by OCoP members, making it challenging to access specific and useful farming information, particularly on shrimp disease, and difficult to revalidate practices in the field. Consequently, farmers prefer to observe their neighbours’ practices and replicate their farming success, given similar ecological prerequisites. To compensate for these shortcomings, it is recommended that context-specific and timely information from conventional extension services be integrated into OCoPs.